Patriarchy In Society Reflected At Henrik Ibsen's A Doll's House (1879): A Feminist Approach - Rachma, Desinta Dhiotya; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi SS, M.Hum (2015)
The research is proposed to analyze the women position which under the control of the invisible hands and the pressures of patriarchal system in society in Henrik Ibsen's A Doll's House by Feminist Approach. The research sets two objectives: first is to analyze the structural elements of play, and second is to analyze the play based on the Feminist Approach. This study is qualitative using the play of Henrik Ibsen's A Doll's House (1879) as the object. There are two kinds of data source: primary and secondary. The primary data source is the play of Henrik Ibsen's A Doll's House and the secondary data source are some literary books and some articles related to the play. The method of collecting data in the reseacrh is library research by reading and summarising the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study is as follows: first, in this drama, Ibsen wants to illustrate how woman are become subordinate in her patriarchal society. Second, the patriarchal system in A Doll's House harms women because they do not have important role in family until they are marginalized and oppresed. The last, the massage conveyed by Henrik Ibsen in A Doll's House is to open an insight especially for women about their social status to do many activities in public to compete with men.